The Wayward Bus Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
The bus driver (Harry Carter) asks for Camille Oaks' (Jayne Mansfield) ticket while another man sleeps on the bus. RESTRICTED USE